Dinâmica temporal e composição florística da comunidade arbórea de floresta ombrófila densa montana, Parque Estadual da Serra do Mar, SP, Brasil - Renó, Isabela Porto [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Atlantic Forest is the second largest tropical rainforest in the Americas but today they remain about 15% of its original vegetation and are essential studies of its remaining for providing valuable information for their conservation. In the Atlantic Forest (Rain Forest) is included vegetation type of the Atlantic rain forest Montane, where the climate is cooler, at altitudes ranging from 500 to 1000 m, but studies of this vegetation are scarce. To enhance understanding about Rain Forest Montana Serra do Mar region (SP), through the structure, temporal changes and floristic composition, the study aims to describe and analyze (a) as the components of the structure and dynamics of tree communities vary in time, (b) how these changes may vary in space and (c) how the floristic composition and similarity between nearby areas. The analysis of the structure and dynamic data were performed using the database containing three censuses, which occurred from 2007 to 2012 (about five years) in four plots (K, L, M and N). Regarding the temporal and spatial changes in the structure of Montane forest, there was a decrease in the density of individuals between censuses, with few differences even between plots; between life forms the trees had higher density than palm trees. Was stable in the basal area over time with a few differences between the portions; in relation to the stock of living biomass above soil was increased over time in all plots. The lowest values in density, basal area and biomass were observed for the plot N. Regarding the diameter classes, the community had a higher density in the smaller diameter classes, and lower density in the larger classes, and found the same pattern between censuses all plots, with changes over the census only in the smaller classes. Both forms of life, trees and palms, were significantly different from each other in relation to the structure, with little variation between censuses. In forest dynamics, there...

A floresta da Mata Atlântica é a segunda maior floresta pluvial tropical do continente americano, porém, restam atualmente cerca de 15% da sua vegetação original, sendo essenciais os estudos de seus remanescentes por fornecerem informações valiosas para sua conservação. Na floresta Atlântica (Floresta Ombrófila Densa) está incluída a fitofisionomia de Floresta Ombrófila Densa Montana, onde o clima é mais frio, em altitudes que variam de 500 a 1200 m, entretanto estudos dessa vegetação ainda são escassos. Visando ampliar o conhecimento sobre Floresta Ombrófila Densa Montana da região da Serra do Mar (SP), através da estrutura, mudanças temporais e composição florística, o presente estudo buscou descrever e analisar (a) como os componentes da estrutura e dinâmica das comunidades arbóreas variam no tempo, (b) como essas mudanças podem variar no espaço e (c) como é a composição florística e similaridade entre áreas próximas. As análises dos dados de estrutura e dinâmica foram realizadas através do banco de dados contendo três censos, que ocorreram de 2007 a 2012 (aproximadamente cinco anos) em quatro parcelas (K, L, M e N). Em relação às mudanças temporais e espaciais na estrutura da Floresta Montana, houve declínio na densidade dos indivíduos entre os censos, com poucas diferenças inclusive entre as parcelas; entre as formas de vida as árvores apresentaram densidade maior do que palmeiras. Houve estabilidade na área basal ao longo do tempo com poucas diferenças entre as parcelas; em relação ao estoque de biomassa viva acima do solo, ocorreu acréscimo ao longo do tempo em todas as parcelas. Os menores valores na densidade, área basal e biomassa foram verificados para a parcela N. Em relação às classes de diâmetro, a comunidade apresentou maior densidade nas menores classes de diâmetro, e menor densidade nas maiores classes, sendo verificado o mesmo padrão entre os censos em todas as parcelas..
Keywords: Plant ecology; Ecologia vegetal; Biomasssa; Florestas - Composição; Florestas tropicais; Mata Atlântica; Mar, Serra do